Biennial bearing in olive (Olea europaea) - Lavee, Shimon (Annales. Series historia naturalis, 2007)
Alternate bearing is a wide spread phenomenon in many fruit tree species and causes severe labor, marketing and thus economical problems. The domestic olive (Olea europaea) is genetically highly alternating in fruit production. The expression of alternate bearing in olives involves a wide range of changesin activation and repression of endogenous metabolic pathways. The degree of alternate bearing is highly dependent on the environmental conditions and might be very different in accordance with the climate in each growing region. The objective of this work was to present the main endogenous and environmental factors and their interactions that lead to alternate bearing and to review approaches with which alternate bearing is reduced.
Keywords: Olea europaea; olive; oljke; rodnost; vpliv okolja